Estimation of possible radiological hazards from natural radioactivity in commercially-utilized ornamental and countertops granite tiles - Turhan, Şeref (Annals of Nuclear Energy 44 (2012) 34–39, 2012)
The aim of this study is to estimate natural radioactivity levels of commercially-utilized ornamental or countertops granite tiles collected from major retailers in Turkey and possible radiological hazards from usage of these materials by calculating external exposure and internal index, indoor absorbed gamma dose rate and the corresponding annual effective dose. The activity concentrations of 226Ra, 232Th and 40K were determined for 42 kinds of different granite tiles using high-resolution gamma-ray spectrometer. The activity concentration of 226Ra, 232Th and 40K varied from 9.2 to 192.5 Bq kg1 (with a mean of 88.4 ± 6.9 Bq kg1 ), 7.5 to 344.6 Bq kg1 (with a mean of 95.3 ± 10.0 Bq kg1 ) and 92.1 to 4155.9 Bq kg1 (with a mean of 1055.2 ± 103.0 Bq kg1 ), respectively. The estimated radiological hazard indices were revised in the light of the relevant national and international legislation and guidance. The values of the radiological hazard indices were found to be within relevant all limit values for superficial materials. The indoor absorbed gamma dose rates estimated from the activity concentrations of 226Ra, 232Th and 40K and the corresponding annual effective doses varied from 4.74 to 85.27 nGy h1 and 0.02 to 0.42 mSv, respectively.
Keywords: Gamma-ray spectrometer, Activity concentration index, Alpha index, External exposure, Annual effective dose